2023
DOI: 10.3390/ijms24043259
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Heterogeneity of Store-Operated Ca2+ Entry in Vascular Endothelial Cells: The Different roles of Orai1 and TRPC1/TRPC4 Channels in the Transition from Ca2+-Selective to Non-Selective Cation Currents

Abstract: Store-operated Ca2+ entry (SOCE) is activated in response to the inositol-1,4,5-trisphosphate (InsP3)-dependent depletion of the endoplasmic reticulum (ER) Ca2+ store and represents a ubiquitous mode of Ca2+ influx. In vascular endothelial cells, SOCE regulates a plethora of functions that maintain cardiovascular homeostasis, such as angiogenesis, vascular tone, vascular permeability, platelet aggregation, and monocyte adhesion. The molecular mechanisms responsible for SOCE activation in vascular endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 244 publications
1
31
0
Order By: Relevance
“…The transmembrane protein STIM1 interacts with ORAI1, which activates CRAC channels, which in turn activates Ca 2+ -selective Icrac currents. STIM1 interacts with TRPC1 to form the STIM-ORAI1-TRPC1 complex and activates the SOCC channel, which facilitates the formation of heterotetrames of the nonselective cation channels TRPC1, TRPC4, and TRPC5 to facilitate further calcium influx ( Moccia et al, 2023 ). It has been shown that TRPC1 is not sufficient to form channels when expressed on it ( Beech, 2013 ).…”
Section: Ion Channels and Tumors On The Cell Membrane That Sense The ...mentioning
confidence: 99%
“…The transmembrane protein STIM1 interacts with ORAI1, which activates CRAC channels, which in turn activates Ca 2+ -selective Icrac currents. STIM1 interacts with TRPC1 to form the STIM-ORAI1-TRPC1 complex and activates the SOCC channel, which facilitates the formation of heterotetrames of the nonselective cation channels TRPC1, TRPC4, and TRPC5 to facilitate further calcium influx ( Moccia et al, 2023 ). It has been shown that TRPC1 is not sufficient to form channels when expressed on it ( Beech, 2013 ).…”
Section: Ion Channels and Tumors On The Cell Membrane That Sense The ...mentioning
confidence: 99%
“…The I CRAC is the primary Ca 2+ -entry pathway sustaining intracellular Ca 2+ oscillations over time in non-excitable cells and mediates an influx of Ca 2+ that is commonly termed store-operated Ca 2+ entry (SOCE) [ 5 , 6 , 57 , 58 ]. SOCE is activated whenever the ER Ca 2+ concentration ([Ca 2+ ] ER ) in proximity of discrete sub-compartments of the peripheral ER falls below a threshold concentration because of ER Ca 2+ release through InsP 3 Rs [ 66 , 67 ].…”
Section: Intracellular Ca 2+ Oscillations Regulate...mentioning
confidence: 99%
“…SOCE is activated whenever the ER Ca 2+ concentration ([Ca 2+ ] ER ) in proximity of discrete sub-compartments of the peripheral ER falls below a threshold concentration because of ER Ca 2+ release through InsP 3 Rs [ 66 , 67 ]. SOCE is mediated by the physical interaction between two ubiquitously expressed proteins ( Figure 3 ): STIM, which is the sensor of [Ca 2+ ] ER , and Orai, which contributes the Ca 2+ -selective channel protein on the plasma membrane [ 5 , 6 , 68 ]. STIM presents two isoforms, i.e., STIM1 and STIM2, whereas Orai displays three paralogues, i.e., Orai1, Orai2, and Orai3.…”
Section: Intracellular Ca 2+ Oscillations Regulate...mentioning
confidence: 99%
See 2 more Smart Citations